Comparison of Maternal and Perinatal Outcome in Pregnant Women with Hypothyroidism Diagnosed before Conception with Hypothyroidism Diagnosed during Pregnancy - Basnet, P; Aggrawal, N; Suri, V; Dutta, P; Mukhopadhyay, K (Journal of Universal College of Medical Sciences, 2014)
BACKGROUND: Thyroid disorder is one of commonest endocrine disorder in women and hence constitutes a common endocrine disorder complicating pregnancy. Diagnosing and treating hypothyroidism preconceptionally and during early pregnancy appears to be a useful strategy to improve maternal and fetal outcome. OBJECTIVE: To compare the maternal and perinatal outcome in pregnant women with hypothyroidism diagnosed preconceptionally with hypothyroidism diagnosed during pregnancy. METHODS: A prospective study. One hundred pregnant women with hypothyroidism at less than 20 weeks Period of Gestation (POG) were recruited for the study and grouped into two groups: Group A-hypothyroidism diagnosed and on treatment before conception, Group B-hypothyroidism diagnosed and started on treatment during pregnancy. Both groups were intensively monitored during pregnancy with serial Thyroid Function Test (TFT) and thyroxine replacement doses were adjusted accordingly. Various maternal, perinatal and fetal outcome measures were studied in both groups prospectively till delivery. RESULTS: The maternal and fetal complications were comparable in the two groups, however the fetal birth weight was significantly higher in Group A versus Group B (2.89±0.485kg vs. 2.70±0.453kg; p=0.039). All the new born babies had normal thyroid function. CONCLUSION: Hypothyroidism diagnosed preconceptionally or during early pregnancy and treated appropriately has beneficial effect on fetal birth weight, and hence the total pregnancy outcome. Screening for thyroid dysfunction should be judiciously performed in all high risk women prior to a planned conception or during their first antenatal visit. DOI: http://dx.doi.org/10.3126/jucms.v2i2.11170 Journal of Universal College of Medical Sciences (2014) Vol.2(2): 21-27